(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Sexual desire could be affected by many psychological and physiological aspects . This research aims to findout the relationship between sexual desire and premenstrual syndrome in young female . A Descriptive designcross-sectional study was carried throughout the present study in order to achieve the study objectives. Theperiod of the study is from 20th September 2019 to 28th April 2020, included 200 young married womenin the reproductive stage, with ages between (17-31) years . Sexual Desire Inventory 3 (SDI-3) has beenused to assess sexual desire after modification to meet the cultural and social considerations . The currentstudy revealed that it explains that the highest percentage of the women subgroup are : women with agesbetween (21-24) years old (50%), those who the age of their husbands (23-26) years old (46.5%), those wholive urban residents (84%), those who they and their husbands work as employee (58.5%), those with barelysufficient monthly income (38.5%), those who are graduated from college or above .The results showedthat there is a significant association (p <0.05) between sexual desire of women and each of : backache,dysmenorrhea and mood instability ; while there is no significant relationship with each of : (backache,breast tenderness, headache, irritability, sadness, aloneness, bloating, vaginal pain, vaginal dryness) . Itis concluded that sexual desire may affected by some symptoms of the premenstrual syndrome . Furtherstudies may be needed to confirms these results .